10.1016/s1558-0164(06)70097-9 (CrossRef Listing of Deleted DOIs, 2000)
Background Periodontal regenerative outcomes are strongly influenced by defect morphology. Maintaining a stable regenerative space under soft-tissue pressure is challenging when treating defects with limited bony support. Methods A 26-year-old female patient presented with hypersensitivity and bleeding during toothbrushing in the maxillary right posterior region. Following initial periodontal therapy, a localized periodontal defect with limited bony support and associated supra-alveolar and interdental-tissue loss persisted between the maxillary right second premolar and first molar. A vestibular incision subperiosteal tunnel access (VISTA)-based tunneling approach was used, and a suspension suture was applied to coronally stabilize the interdental soft tissue before placement of recombinant human fibroblast growth factor-2-impregnated freeze-dried bone allograft. A resorbable collagen membrane and connective tissue graft were placed on the buccal aspect to support graft containment and wound stability. Results At 12 months, probing depths remained within 2-3 mm, with a maximum clinical attachment gain of 4 mm. Improved soft-tissue contours, partial root coverage, and radiographic defect fill were maintained. Conclusions This case suggests that the Suspension-Created Regenerative Envelope (SCREEN) concept, which involves suspension-created stabilization of a regenerative envelope before graft placement, may be a useful adjunctive strategy for managing periodontal defects with limited bony support. Key points The Suspension-Created Regenerative Envelope (SCREEN) concept describes suspension-created stabilization of a regenerative envelope before graft placement in a periodontal defect with limited bony support. A VISTA-based approach allowed preservation of the marginal gingiva and interdental papilla while facilitating coronal stabilization of the interdental soft tissue. At 12 months, probing depth reduction, clinical attachment gain, improved soft tissue architecture, and radiographic defect fill were maintained; however, longer follow-up is needed to evaluate stability and reproducibility. Plain language summary Some periodontal defects are difficult to treat because the missing bone does not provide enough support to hold the healing tissues and grafting material in a stable position. In this case, a young female patient had a localized periodontal defect with gingival recession, loss of tissue between the teeth, tooth sensitivity, and bleeding during toothbrushing. A tunnel-type surgical approach was used to avoid cutting the gingival tissue between the teeth. Before placing the bone-grafting material, the interdental soft tissue was carefully repositioned and stabilized in a more coronal position using a suspension suture. This created a protected space for healing. The space was then filled with grafting material containing a growth factor, and soft tissue was added on the buccal side to improve tissue thickness and stability. At 12 months, the treated site showed shallow probing depths, clinical attachment gain, improved gingival contour, radiographic defect fill, and sustained improvement in the patient's symptoms. Because this is a single case, a longer follow-up and additional cases are needed.